Research on the Construction and Practice of an Urban–Rural Integration Planning Model from the Perspective of Element Flow: A Case Study of Xiuzhou District, Jiaxing City - Sen Zhang; Keke Sun; Haoge Zhao; Hong Yao; Lei Shen (Land)
Ensuring the healthy movement of urban and rural factors is a key aspect in promoting urban–rural integration. Defining the mechanisms of factor movement and constructing an urban–rural integration planning model are important for the practice of urban–rural integration work. This study considers the movement of urban and rural factors as its entry point and explores the resource endowments and movement paths of urban and rural factors based on the city–town–village spatial system. The urban–rural integration planning model was constructed using spatial and policy dimensions, and six integration design strategies for ecological, population, industrial, land, transportation, and public service factors were defined. Next, considering the Xiuzhou District of Jiaxing City as a case study, this study combines the current characteristics and integration directions of urban and rural factors to propose integration design goals and measures for six key factors. The movement paths of urban and rural factors were delineated, and the specific tasks of each administrative entity in urban–rural integration development were identified at each level to achieve the breakdown and transmission of the overall urban–rural integration strategy. The study integrated current status assessment, integration design, path construction, and goal breakdown, exploring the formulation of urban–rural integration strategies and work pathways. The aim was to address the current gap between urban–rural integration theory and practice, thus providing a reference and inspiration for related research.